Keeping Race at the Center of School Discipline Practices and Trauma-Informed Care: An Interprofessional Framework. Issue 3 (3rd August 2020) - Joseph, Andrea Asha; Wilcox, Serena M; Hnilica, Rebecca J; Hansen, Mary C
Abstract: Given the unique forms of trauma that some Black and Brown youths are exposed to, and the salience of race and racial bias in discipline decision making, this article proposes that discipline interventions should be both race centered and trauma informed. Using critical race theory (CRT), trauma-informed practice literature, and restorative practice philosophies, this article presents a framework that highlights how schools can incorporate racial equity into mental health practices and discipline decision making with students. Namely, CRT tenets such as the centrality of race and racism, challenging the dominant perspective, valuing experiential knowledge, and the commitment to social justice guide authors' recommendations on discipline decision making. Using an interprofessional perspective, this framework delineates how school social workers, school psychologists, and school counselors can support their schools to integrate interprofessional, trauma-informed, and race-centered practices into a behavioral intervention. Ultimately, this article provides interpersonal, practice, and structural recommendations that can help practitioners engage in equitable discipline decision making.